Intersecting Mechanisms of Hypoxia and Prostaglandin E2-Mediated Inflammation in the Comparative Biology of Oral Squamous Cell Carcinoma - Nasry, Walaa Hamed Shaker; Martin, Chelsea K. (Frontiers in Oncology, 2021)
The importance of inflammation in the pathogenesis of cancer was first proposed by Rudolph Virchow over 150 years ago, and our understanding of its significance has grown over decades of biomedical research. The arachidonic acid pathway of inflammation, including cyclooxygenase (COX) enzymes, PGE2 synthase enzymes, prostaglandin E2 (PGE2) and PGE2 receptors has been extensively studied and has been associated with different diseases and different types of cancers, including oral squamous cell carcinoma (OSCC). In addition to inflammation in the tumour microenvironment, low oxygen levels (hypoxia) within tumours have also been shown to contribute to tumour progression. Understandably, most of our OSCC knowledge comes from study of this aggressive cancer in human patients and in experimental rodent models. However, domestic animals develop OSCC spontaneously and this is an important, and difficult to treat, form of cancer in veterinary medicine. The primary goal of this review article is to explore the available evidence regarding interaction between hypoxia and the arachidonic acid pathway of inflammation during malignant behaviour of OSCC. Overlapping mechanisms in hypoxia and inflammation can contribute to tumour growth, angiogenesis, and, importantly, resistance to therapy. The benefits and controversies of anti-inflammatory and anti-angiogenic therapies for human and animal OSCC patients will be discussed, including conventional pharmaceutical agents as well as natural products.